An effector region in Eps8 is responsible for the activation of the Rac-specific GEF activity of Sos-1 and for the proper localization of the Rac-based actin–polymerizing machine - Scita, Giorgio (The Rockefeller University Press, 2001)
Genetic and biochemical evidence demonstrated that Eps8 is involved in the routing of signals from Ras to Rac. This is achieved through the formation of a tricomplex consisting of Eps8–E3b1–Sos-1, which is endowed with Rac guanine nucleotide exchange activity. The catalytic subunit of this complex is represented by Sos-1, a bifunctional molecule capable of catalyzing guanine nucleotide exchange on Ras and Rac. The mechanism by which Sos-1 activity is specifically directed toward Rac remains to be established. Here, by performing a structure–function analysis we show that the Eps8 output function resides in an effector region located within its COOH terminus. This effector region, when separated from the holoprotein, activates Rac and acts as a potent inducer of actin polymerization. In addition, it binds to Sos-1 and is able to induce Rac-specific, Sos-1–dependent guanine nucleotide exchange activity. Finally, the Eps8 effector region mediates a direct interaction of Eps8 with F-actin, dictating Eps8 cellular localization. We propose a model whereby the engagement of Eps8 in a tricomplex with E3b1 and Sos-1 facilitates the interaction of Eps8 with Sos-1 and the consequent activation of an Sos-1 Rac–specific catalytic ability. In this complex, determinants of Eps8 are responsible for the proper localization of the Rac-activating machine to sites of actin remodeling.